IMF Survey : Volume 28, Issue 07. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1999)
IMF Managing Director Michel Camdessus visited Moscow from March 27 to March 29 and met with Russian Prime Minister Yevgeny Primakov and other senior officials. On March 29, Camdessus and Primakov issued a joint communique, the text of which follows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet